The electrical activity (EMG) of the triceps brachii and golf muscles during the motor learning stages of the peaceful scoring skill in basketball (Journal of the College of Basic Education, 2022)
The importance of the research lies in knowing the electrical activity during the learning stages of the triceps brachii muscle and the golfer's muscle during the three motor learning stages (rough - accurate - automated) in the skill of peaceful scoring in basketball, while the research problem lies in the lack of a clear view of what happens in the electrical activity During the three motor learning stages of the triceps brachii muscles and golf. The research objective was to identify the electrical activity during the motor learning stages of the triceps and golf muscles in the peaceful scoring skill in basketball.